The Management of chronic wounds: a current review for internal medicine physicians - Buczek, Sylwia Czesława; Byjoś, Ewa; Fabiś, Katarzyna; Zbylut, Mateusz; Mateja, Patrycja; Mstowska, Weronika; Milewska, Kamila; Bury, Karolina; Młynarczyk, Katarzyna; Naliuka, Hanna (Journal of Education, Health and Sport, 2026)
Background: Chronic wounds are a growing clinical problem in older patients especially those with multimorbidity. Their healing is impaired by constant inflammation, skin cell dysfunction and bacterial biofilm presence. Aim: The aim of this review article is to present the current management of chronic wounds in internal medicine practice. Methodology: The study was conducted as a narrative review. A structured literature search was carried out using the following electronic databases: PubMed,Scopus, Web of Science, and Google Scholar. The search included publications released mainly between 2017 and 2025, in order to reflect current clinical practice and guideline recommendations. Results: The reviewed literature and articles confirm that internal medicine doctors play a key role in the chronic wound treatment. Firstly, they should concentrate on the etiology of the wound. Comorbidities are also worth considering. The TIME strategy is a structured framework for dealing with wounds. Selected additional therapies are mentioned including negative pressure wound therapy and larval therapy which are used to improve debridement and reduction of bacterial biofilm. All of these actions contribute to reducing the risk of complications, hospitalizations and amputations. Conclusion: Chronic wounds are still a complex and heterogeneous clinical problem. It requires an individualized diagnostic and therapeutic approach based on etiology. The internist actions are essential in early patient assessment, management of comorbidities and coordination of multidisciplinary care. In some cases advanced therapies such as negative pressure wound therapy or larval therapy need to be performed in order to achieve a better outcome.